HEALTH PROMOTION INFLUENCES ON KNOWLEDGE OF WOMEN'S MENOPAUSE IN RURAL - Srimiyati (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Background the incidence of menopausal syndrome in Indonesia is 12.5% while the incidence fear of facing menopause in Wonogiri district 35.5%. Improvement in community health status is carried out throughout the life cycle since infants, toddlers, school age children, adolescents, adults to the elderly. Premenopausal women are important to have understanding of menopause. Health promotion is one way to change cognitive to establish conducive healthy behavior. The purpose this study aims to knowing the effect of health promotion on menopause knowledge. Method of this research was pre experimental with approximation one group pre test post test design without a control group. This research was conducted at Hamlet Sendangagung, Sendangmulyo and Sendangsari. The sample size was 100 premenopausal women, taken with multistage sample technique. The instrument used is a questionnaire knowledge about menopause. The data analysis which done is by using Kolmogorov-smirnov and Wilcoxon test with confidence interval 95% and ?= 0,05. Result the average pre test score of knowledge before being given health promotion about menopause was 14,73. While the average value of post test of knowledge after given health education equal to 17,38, the increase of 2,75 poin. Result of this research indicated an increased respondents with good knowledge from 44 respondents (44%) became 79 respondents (79%) after inform the health promotion. Result of Wilcoxon test was P–value = 0,000 < 0,05 indicated a significant difference between the menopausal knowledge before and after inform the health promotion. Conclusions and recommendations that the health promotion giving a significant influence to knowledge about menopausal. Researchers can further increase knowledge about menopause with different methods and media.